Varying Presentations of Multisystem Inflammatory Syndrome Temporarily Associated with COVID-19 - Jasmina Krikilion; Lisa Nuyttens; Siel Daelemans; Karlien François; Reiner Mauel; Daniel De Wolf; Gerlant van Berlaer (Case Reports in Pediatrics)
Background. A novel coronavirus identified in 2019 leads to a pandemic of severe acute respiratory distress syndrome with important morbidity and mortality. Initially, children seemed minimally affected, but there were reports of cases similar to (atypical) Kawasaki disease or toxic shock syndrome, and evidence emerges about a complication named paediatric inflammatory multisystem syndrome temporarily associated with SARS-CoV-2 (PIMS-TS) or multisystem inflammatory syndrome in children (MIS-C). Case Presentations. Two cases were compared and discussed demonstrating varying presentations, management, and evolution of MIS-C. These cases are presented to increase awareness and familiarity among paediatricians and emergency physicians with the different clinical manifestations of this syndrome. Discussion. MIS-C may occur with possible diverse clinical presentations. Early recognition and treatment are paramount for a beneficial outcome.